Differences in Gender and Overall Survival for Temperature-Sensitive TP53 Mutations in Gastroesophageal Cancer - Shaikh, Danial H.; Park, Margaret; Chen, Jiandong; Huang, Jeffrey; Friedman, Mark S.; Dam, Aamir N.; Luthra, Anjuli K.; Cappelle, Saraswathi; Pena, Luis R.; Permuth, Jennifer B.; Mok, Shaffer R. S. (Medicina (Kaunas, Lithuania), 2024)
Background and Objectives: Temperature-sensitive (TS) mutants of TP53 are thermally unstable, unfolded, and inactive at body temperature but can be refolded and reactivated at sub-physiological temperatures. TS TP53 may be amenable for functional rescue by hypothermia or structure-stabilizing drugs, and may retain low-level transcriptional activity at 37 °C. TP53 mutations are observed in 47% of all esophageal cancers (ECs) and 25% to 40% of gastric cancers (GCs). We aimed to investigate the trends and outcomes of EC and GC with TS TP53 mutations using cBioportal. We hypothesize that TS TP53 mutants in EC and GC present a unique prognostic profile distinct from non-TS TP53 mutants, potentially affecting overall survival and cancer progression. Materials and Methods: We identified 1924 patients from cBioportal with GC or EC, harboring any TP53 mutation. Patients were then stratified based on the TP53 temperature sensitivity according to a recently reported functional analysis of its activity. Patients were also stratified based on a history of Barrett’s esophagus (BE), cancer stage, sex, and race. We then compared populations (TS vs. non-TS TP53) to assess differences and evaluated survival outcomes. Results: Males represented 77% of the cohort, and 51.6% of the samples were from patients with stage IV cancer. No association was found between TS vs. non-TS mutational status and BE, cancer stage, or race. Interestingly, a significantly higher proportion of females (22.9%) than males (14.5%) displayed a TS TP53 mutation (p = 0.012). No significant difference was seen in overall survival between the TS and non-TS mutations capable of ≥50% growth suppression at 32 °C (median = 33 vs. 28 months, p = 0.36). This trend was also observed when the patients were filtered based on cancer location. The median survival for EC was 32.5 months compared to 33 months (p = 0.67). In cases of GC, median survival times could not be determined due to the insufficient number of events. Conclusions: Although no statistical significance was observed, a decrease in overall survival for patients with TS TP53 mutations was noted. The result is counterintuitive given that TS mutants have less severe structural destabilization and suggests TS TP53 mutations may have a unique prognostic value that warrants further investigation.